Hubungan Motivasi Belajar Berbasis Expectancy-Value Theory dengan Hasil Belajar Pjok pada Siswa Kelas IV Sekolah Dasar di Kecamatan Cimalaka - Deddy Iqbal; Dinar Dinangsit; Encep Sudirjo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the relationship between learning motivation and learning outcomes in Physical Education, Sports, and Health (PJOK) among fourth-grade elementary school students in the Cimalaka District. The method used was a quantitative approach with a correlational design through an ex post facto method. The sample consisted of 40 students selected using a multistage sampling technique. Data collection instruments included a learning motivation questionnaire adapted from the Expectancy–Value Theory and documentation of authentic PJOK learning outcomes. The results showed a significant positive relationship between learning motivation and PJOK learning outcomes. In conclusion, learning motivation is an important factor in determining PJOK learning outcomes; therefore, strengthening expectancy and task value aspects is essential in the learning process.   Keywords: Elementary School, Expectancy-Value, Learning Motivation, PJOK Learning Outcomes.